Alveolar concentration of nitric oxide predicts pulmonary function deterioration in scleroderma. Issue 2 (24th October 2011) - Tiev, Kiet Phong; Hua-Huy, Thong; Kettaneh, Adrien; Allanore, Yannick; Le-Dong, Nhat-Nam; Duong-Quy, Sy; Cabane, Jean; Dinh-Xuan, Anh Tuan
Abstract : Background: Respiratory failure is a life-threatening and unpredictable complication of systemic sclerosis (SSc). A study was undertaken to assess the value of alveolar nitric oxide (NO) in predicting the risk of lung function deterioration leading to respiratory failure or death in patients with SSc. Methods: 105 patients with SSc were enrolled in this prospective cohort and were followed longitudinally over a 3-year period during which the risk of occurrence of deleterious events was analysed according to alveolar concentration (CA no ), conducting airway output (J′aw no ) and fractional concentration (FE no 0.05 ) of exhaled NO measured at inclusion. Comparison was made between each NO parameter to predict the occurrence of deleterious events, defined as a 10% decrease in total lung capacity or forced vital capacity from baseline, or death. Results: The area under the receiver operating characteristic curve of CA no to predict the occurrence of the combined events was 0.84 (95% CI 0.76 to 0.92; p<0.001), which was significantly higher than those of J′aw no and FE no 0.05 (p<0.001). A cut-off of CA no of 5.3 ppb had a sensitivity of 88% and a specificity of 62% for the prediction of the occurrence of combined events during follow-up, and was validated in an independent cohort of patients with SSc. Combined events occurred more frequently in patients whose CA no was >5.3 ppb. The adjusted HR for patients with CA no >5.3 ppb was 6.06 (95% CI 2.36 to 15.53; p<0.001). CA no accurately predicted the occurrence of combined events irrespective of forced vital capacity values or the presence of interstitial lung disease at baseline. Conclusions: Increased CA no accurately identifies patients with SSc with a high risk of developing lung function deterioration and may help to initiate early appropriate treatment.